2006
DOI: 10.1039/b511010f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanopatterned films of bovine serum albumin and staphylococcal protein A using latex particle lithography

Abstract: Arrays of protein nanostructures can be formed on surfaces such as mica(0001) and Au(111) using lithography with polystyrene latex particles. To create arrays of protein nanostructures, monodisperse latex spheres are mixed with the desired protein (e.g. BSA, protein A or IgG) and deposited onto substrates. Protein-coated nanospheres self-assemble into organized crystalline layers when dried on flat surfaces. After rinsing with water, dried latex spheres are displaced to expose periodic arrays of uncovered circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…The multicomponent patterns were revealed after the silica spheres mask was removed by sonication in H 2 O for 3 s. To retain bioactivity and prevent detachment, sonication time was kept under 1 min. 45 …”
Section: Methodsmentioning
confidence: 99%
“…The multicomponent patterns were revealed after the silica spheres mask was removed by sonication in H 2 O for 3 s. To retain bioactivity and prevent detachment, sonication time was kept under 1 min. 45 …”
Section: Methodsmentioning
confidence: 99%
“…A simple approach to functional protein array production which is based on selfassembling of polymer templates and proteins has recently been developed [114,115]. To create arrays of protein nanostructures with defined spacing, monodisperse latex spheres have been coated with the desired protein (BSA, proteins A and G) and deposited on a mica (001) or gold (111) surface.…”
Section: Combination Of Nsl and Other Lithographic Approachesmentioning
confidence: 99%
“…After drying, latex particles are displaced to expose periodic arrays of immobilized proteins, which remain attached to the surface and maintain the order and periodicity of the latex scaffold. The morphology and diameter of protein nanostructures thus prepared are tunable by setting up the protein/latex ratio and the diameter of latex spheres [114]. Similarly, lysozyme periodic nanostructures have been prepared on silicon by NSL, retaining their full activity [115].…”
Section: Combination Of Nsl and Other Lithographic Approachesmentioning
confidence: 99%
“…The fabrication of nanopatterned films of protein by NSL yielding ring shaped structures has been demonstrated (Garno, Amro et al 2002;Li, Henry et al 2006). In particular it was shown that proteins deposited in this manner retained the capability to bind specifically to immunoglobulin molecules (Garno, Amro et al 2002).…”
Section: Applications Of Nsl In Biology and Biotechnologymentioning
confidence: 99%